Correlates of Awareness and Attitude Regarding HIV / AIDS Transmission in Pregnant Females Attending Tertiary Care Center of Southern Rajasthan - Reshma Reja; Rekha Bhatnager; Atul Kumar Gupta; Arun Singh (Medsci Publications, 2018)
Introduction: HIV causes morbidity and mortality in infants and children, pertaining to its Parent- to-child transmission (PPTCT) risk. PPTCT is responsible for 90% childhood HIV infection. Pre- sent study was done to assess the awareness regarding HIV/AIDS transmission in pregnant women and their attitude towards peo- ple living with HIV/ AIDS (PLHA). Methodology: It was a hospital based cross-sectional study con- ducted on pregnant women attending antenatal clinic at M.B Hos- pital. 320 pregnant mothers were interviewed using a semi struc- tured questionnaire. Results : Out of 320 pregnant females majority were of age group 20-25 years ,68%were housewives.77% mothers knew that HIV is transmitted by sexual route.30% of the mothers thought that one could get infected by merely touching an HIV positive people. The association of knowledge score with educational status and resi- dential status is highly significant (p<0.001). Conclusion: The awareness regarding HIV/AIDS is still low, so there is a need to focus on I.E.C. activities.